2020
DOI: 10.1002/term.3138
|View full text |Cite
|
Sign up to set email alerts
|

TLR4, RAGE, and p‐JNK/JNK mediated inflammatory aggression in osteoathritic human chondrocytes are counteracted by redox‐sensitive phenolic olive compounds: Comparison with ibuprofen

Abstract: Osteoarthritic chondrocytes show an over‐activity of inflammatory catabolic mediators, and olive products have attracted attention because they were discovered to have some benefits on osteoarthritis patients. We investigated the mechanisms of action of olive leaf polyphenolic compounds in osteoarthritic chondrocytes (OACs) using a standardized leaf extract, ZeyEX, and its main phenolic component, oleuropein, also compared with anti‐inflammatory drug ibuprofen. OACs, isolated from joint‐cartilages of Grade 4 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Therefore, it is speculated that BIIP can reduce OA by downregulating the p-JNK protein expression in a dose-dependent manner, consistent with the results of Elmazoglu. 50…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is speculated that BIIP can reduce OA by downregulating the p-JNK protein expression in a dose-dependent manner, consistent with the results of Elmazoglu. 50…”
Section: Resultsmentioning
confidence: 99%
“…NaIHS would negatively modulate: IL-1β, 13 IL-4, 27 IL-6, 13 IL-8, 27 IL-10, 27 IL-18, 24 tumour necrosis factor-alpha (TNFα), 13 interferon-gamma (IFN-γ), 13 transforming growth factor-beta 1 (TGF-β1), 13 intercellular adhesion molecule-1 (ICAM-1), 13 vascular adhesion molecule-1 (VCAM-1), 28 Eselectin, 12 monocyte chemoattractant protein 1 (MCP-1), 27 chemokine (C-C motif) ligand 2 (CCL2), 27 growth factors granulocyte-macrophage colony-stimulating factor 29 and hepatocyte growth factor (HGF). 27 Through its effect on the above possible negative modulation of pro-inflammatory cytokines responsible for the processes of adhesion, migration, neutrophil NOD-like receptor protein 3 (NLRP3) inflammasome inhibition 22 : by cyclooxygenase 2 (COX2) inhibition effect, it might inhibit NLRP3 inflammasome activation, 24 which significantly reduces the levels of caspase-1, 24 interleukin-1β (IL-1β), 24 IL-18 24 and gasdermin-D (GSDMD) 24 ; NaIHS might inhibit NLRP3 inflammasome activation due to its agonist peroxisome proliferator-activated receptor-gamma (PPAR-γ) effect 21,23 and it might also inhibit NLRP3 inflammasome via inhibition of membrane volume anion chloride channel 23,25 ;…”
Section: Negative Modulation Of Main Pro-inflammatory Cytokines Uncon...mentioning
confidence: 99%
“…IL‐8, 27 IL‐10, 27 IL‐18, 24 tumor necrosis factor‐alpha (TNF‐α), 13 interferon‐gamma (IFN‐γ), 13 transforming growth factor‐beta 1 (TGF‐β1), 13 intercellular adhesion molecule‐1 (ICAM‐1), 13 vascular adhesion molecule‐1 (VCAM‐1), 28 E‐selectin, 12 monocyte chemoattractant protein 1 (MCP‐1), 27 chemokine (C‐C motif) ligand 2 (CCL2), 27 growth factors granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) 29 and hepatocyte growth factor (HGF) 27 ; (3) Down‐regulation of nitric oxide (NO) hyperproduction : see Table 3; (4) Inhibition of the main local inflammatory mediators : by COX2 inhibition effect, it may inhibit prostaglandins, 12 prostacyclins, 12 histamine, 38 bradykinins 6,33,39 and NO 31 and (5) Antiangiogenic effect : by COX‐2 inhibition effect, it would negatively modulate vascular endothelial growth factor (VEGF), 40,42 basic fibroblast growth factor (bFGF), 40,42 CCL2, 27 HGF, 27 extracellular signal‐regulated kinase 2 (ERK2), 40 mitogen‐activated protein kinase (MAPK), 40 cyclin‐dependent kinase 1/2 (CDK 1/2), 40 checkpoint kinase 1 (CHK1), 40 cyclin A, 40 via Apelin/G protein‐coupled receptor (APJ) 40 and, by COX‐independent effect, NaIHS would inhibit hypoxia inducible factor‐1 alpha (HIF‐1α) 37 and HIF‐2α 43 . .…”
Section: Potential Therapeutic Effects Of Naihs In Pneumonia and Card...mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few years, a number of polyphenols have been investigated regarding the mechanisms underlying their effects on OA ( Figure 1 ). It has been shown that HT can regulate sirtuin (SIRT)-6-mediated autophagy in chondrocytes [ 64 ] and oleuropein can suppress the NF-κB and MAPK signaling pathways [ 65 , 66 ]. Resveratrol is another polyphenol that promotes chondrocyte autophagy via regulation of the regulating AMPK/mTOR signaling pathway [ 67 ].…”
Section: Conclusive Remarks and Future Perspectivesmentioning
confidence: 99%